Indoor Sound Pressure Level From Service Equipment in Buildings: Influence of Testing Methods on Measurement Results - NOWICKA, Elżbieta; SZEWCZAK, Ewa (Archives of Acoustics, 2021)
Indoor noise can greatly affect the health and comfort of users, so the significance of the right assessment of the compliance with the requirements is obvious. But noise level testing is carried out using different methods, which may not ensure consistency in assessments.The paper presents the influence of test methods on measurement results determined based on an analysis of inter-laboratory comparative studies. The analyses presented in the paper apply to an equivalent sound pressure level determined for a permanent source of sound – an air-conditioning device. The test methods were characterised according to their precision. In order to compare them, their compatibility was analysed based on the methodology described in the literature, alongside a single-factor analysis of variance. It was determined that there were no grounds for rejecting the hypothesis about lack of statistical differences between the results obtained via different methods. Each of the methods is characterised by different precision, so consequently the same result obtained with each method carries a different risk in regards to noise assessment.The reason for taking up this kind of research was the decision of the Polish Technical Committee in 2018 about introducing new acoustic requirements in Poland concerning the admissible indoor sound pressure levels. It was decided to implement new international methods of testing indoor sound pressure levels emanating from the service equipment in the building. It was necessary to show the differences between the current method and its new counterparts.